Interphragmental debridement and percutaneous reduction of displaced humeral supracondylar fracture - José Julio Requeiro Molina; Ana María Machado Consuegra; Leobys Kautets Pardiñas de León; Liyanira Alonso Leiva; Juana María Morejón Fernández; Gabriela María Requeiro Molina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Supracondylar humerus fracture has a high incidence in the first decade of life. It represents 3-16% of all fractures in children, only surpassed by radius distal fracture; it also constitutes 53-67% of elbow fractures in this age group. The magnitude of the fragments displacement, the severity of soft tissue lesions and the possibility of neurovascular complications, make it a serious injury requiring emergency treatment. In certain cases the fracture local conditions the prevent the fragments adequate manipulation, so the reduction is not achieved in the correct way and the fixation is unstable, requiring surgical intervention to achieve reduction. In this article a new method is presented that achieves the anatomical reduction and allows stable fixation by percutaneous way. In addition, the results obtained in two clinical cases in which this method was applied are shown.